Soggetto trascendentale, mondo della vita, naturalizzazione. Uno sguardo attraverso la fenomenologia di Edmund Husserl - Miniagio, Gabriele (Premio Ricerca «Città di Firenze», 2012)
This work intends to make a theoretical critique of naturalization, not in the name of transcendental idealism, but in that of a new phenomenology of complexity, while seeking its essential concepts. In this, the crisis of the sciences, the tendency to forget subjective experience and the human world in the broad sense, is traced back, not to the inability to go beyond the level of natural-objective knowledge towards a transcendental fundament, but to the inability to remain there and explore the multiple organizational levels of what is given in it. In this perspective, investigating consciousness as a set of real states and acts within an objective world that exists and has its structures must lead, not to the reduction of subjective experience, but to the complexification of reality. The theoretical critique of naturalization is carried out as part of a genealogical analysis, making it emerge as a tool of biopower, a discursive practice with a performative nature, whose result, perfectly suited to late cognitive capitalism, is to produce that same naturalized subjectivity which it theoretically enunciates.